In vitro effect of chlorhexidine gel on torque and detorque values of implant abutment screw - Hamid Neshandar Asli; Bardia Vadiati Saberi; Arezoo Sadat Fatemi (Wolters Kluwer Medknow Publications, 2017)
Purpose: Use of chlorhexidine (CHX) gel to eliminate the malodor of implant cavity may decrease the friction coefficient and effective preload and result in abutment screw loosening. This study aimed to assess the effect of CHX gel on the preload, torque, and detorque values. Materials and Methods: This in vitro experimental study was conducted on three groups of five implants. Group A (G1) was the control group and no material was applied to the implant cavity. In Group B (G2), implant cavity was filled with saliva before abutment screw tightening. In Group C (G3), implant cavity was first filled with saliva and then with CHX gel. The abutments were torqued to 24 N/cm2 according to the manufacturer's instructions and were then loosened. These processes were repeated five times. The ratio of the mean percentage of detorque to torque values was measured in all groups. The collected data were analyzed using ANOVA and post hoc Tukey's test. Results: No significant difference was noted between G1 and G2. Group G2 had significantly higher detorque value (p < 0.05). ANOVA detected a significant difference in the mean torque (p < 0.05) and detorque (p < 0.001) values among the three groups. G3 showed maximum difference between torque and detorque values; the minimum difference was noted in G2. Conclusion: Application of CHX gel (to decrease the malodor of the implant cavity) decreases the detorque and preload values and increases the risk of screw loosening.